Elevated vesicular Zn2+ in dorsal root ganglion neurons expressing the transporter TMEM163 causes age-associated itchy skin in mice. - Fang Tong; Shuai Liu; Chen Zhang; Xicheng Gu; Huan Yang; Bin Zhou; Yun-Yun Wang; Jianwei Chen; Qianhui Qu; Ye Gong; Haili Pan; Chen Liang; et al. (PLoS Biology)
The prevalent itching condition associated with aging, historically referred to as senile pruritus, diminishes quality of life. Despite its impact, effective treatments remain elusive, largely due to an incomplete understanding of its pathological cause. In this study, we reveal a subset of dorsal root ganglion neurons enriched with Zn2+ that express the vesicular Zn2+ transporter TMEM163. These neurons form direct synapses with and modulate the activity of spinal NPY+ inhibitory interneurons. In aged mice, both the expression of TMEM163 and the concentration of vesicular Zn2+ within the central terminals of TMEM163+ primary afferents show marked elevation. Importantly, the excessive release of vesicular Zn2+ significantly dampens the activity of NPY+ neurons, triggering the disinhibition of itch-transmitting neural circuits and resulting in chronic itch. Intriguingly, chelating Zn2+ within the spinal dorsal horn effectively relieves itch in aged mice. Our study thus unveils a novel molecular mechanism underlying senile pruritus.